KEPASTIAN HUKUM DALAM INOVASI LAYANAN KESEHATAN BERBASIS TEKNOLOGI: STUDI PUSTAKA ATAS REGULASI TELEMEDICINE DI INDONESIA - Gunawan Widjaja; Wagiman; Dyah Ersita Yustanti; Hotmaria Hertawaty Sijabat; Handojo Dhanudibroto (Jurnal Kesehatan, 2025)
The development of digital technology has brought significant transformations in healthcare services, particularly through the implementation of telemedicine in Indonesia. This innovation opens up enormous opportunities to expand access, improve efficiency, and support the equitable distribution of medical services, especially in remote areas. However, it should be noted that regulations governing telemedicine in Indonesia are still sectoral and partial in nature, dominated by Minister of Health Regulation No. 20 of 2019, the Health Law, and the Personal Data Protection Law. These regulations have not fully addressed challenges related to legal certainty, patient data protection, and the legal responsibilities of healthcare professionals and service providers. This literature review analyses the legal framework for telemedicine in Indonesia, identifies regulatory challenges, and highlights the need for harmonisation and the development of more comprehensive regulations to ensure that digital health service innovations can operate safely, fairly, and provide optimal protection for all parties. It is hoped that the findings of this study will contribute to policy development and strengthen the legal system in addressing the rapid development of telemedicine in Indonesia.